Ciprofloxacin-Mediated Mutagenesis Is Suppressed by Subinhibitory Concentrations of Amikacin in Pseudomonas aeruginosa - Valencia, Estela Ynés (Antimicrob Agents Chemother, 2017)
Resistance to antibiotics is a global health problem. Activation of the SOS response, and the subsequent elevation in mutagenesis, contributes to the appearance of resistance mutations. Among currently used drugs, quinolones are the most potent inducers of the SOS response. In the present study, we show that amikacin inhibits ciprofloxacin-mediated SOS induction and mutagenesis in Pseudomonas aeruginosa.